Competency of Digital Technology: The Maturity Levels of Teachers and Students in Vocational Education in Indonesia - Astuti, Melinda; Arifin, Zainal; Mutohhari, Farid; Nurtanto, Muhammad (Journal of Education Technology, 2021)
One of the needs for competence in the world of work in the 21st century and the era of the industrial revolution 4.0 is competence in using digital technology. The maturity of digital technology in supporting industrial 4.0 competencies has received less serious attention from vocational education. Teachers still have a low level of maturity in mastering digital technology. This study aims to analyze the maturity level of teachers and students in vocational education in mastering learning using digital technology. The survey research uses a design developed by Rea & Parker. A total of 233 vocational high school students were included as the research sample. Data were collected using a questionnaire technique with a four Likert scale questionnaire instrument. The collected data were analyzed using descriptive statistics and inferential statistics t-test. The results show that the maturity level of digital technology for teachers and students is sequential, starting from caring, literacy, capability, creativity, and being critical of using digital technology. All levels of maturity are included in the low category. Various training and learning innovations relevant to digital technology mastery competencies are significant to be improved.